2005
DOI: 10.1097/01.don.0000145034.10218.3f
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of In Vitro Retrograde Obturation Materials

Abstract: The purpose of this review was two-fold: (a) to determine which retrograde obturation material(s) best prevents dye/ink penetration in vitro; and (b) to determine whether in vitro results agree with in vivo results. A MEDLINE search was conducted to identify in vitro studies published between January 1966 and October, week 4, 2003, conducted on human teeth, and published in English, German, or French language, testing the resistance to retrograde penetration of retrograde filling materials. The MEDLINE search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
0
15
0
3
Order By: Relevance
“…These results agree with the results obtained by Sullivan et al (11) and Fogel et al (14) who had used fluid filtration model and reported no statistical differences between the microleakage with SuperEBA and IRM. Nevertheless, Theodosopoulou and Niederman (26) systematically reviewed studies concerned with retrograde obturation materials evaluated in vitro by dye/ ink penetration method. They reported that SuperEBA cement provided a less effective sealing than IRM and orthograde gutta-percha and sealer after 10 days, based on the linear regression analysis (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results agree with the results obtained by Sullivan et al (11) and Fogel et al (14) who had used fluid filtration model and reported no statistical differences between the microleakage with SuperEBA and IRM. Nevertheless, Theodosopoulou and Niederman (26) systematically reviewed studies concerned with retrograde obturation materials evaluated in vitro by dye/ ink penetration method. They reported that SuperEBA cement provided a less effective sealing than IRM and orthograde gutta-percha and sealer after 10 days, based on the linear regression analysis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Theodosopoulou and Niederman (26) systematically reviewed studies concerned with retrograde obturation materials evaluated in vitro by dye/ ink penetration method. They reported that SuperEBA cement provided a less effective sealing than IRM and orthograde gutta-percha and sealer after 10 days, based on the linear regression analysis (26). However, in the studies included in the review IRM was examined over a period ranging from 0 to 7 days whereas SuperEBA and orthograde condensed gutta-percha with sealer were examined over periods of time ranging from 0 to 84 days and 0.1 to 180 days, respectively (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been employed to assess the sealing ability of materials used for filling root canals [12][13] . An in vitro dye penetration test is usually used as an easy, quantitative method for assessing the leakage of materials used for endodontic filling [14][15] . An India ink solution is a potentially suitable tracer because some carbon particles have relatively similar sizes to bacteria, and thus would show similar degrees of penetration 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been employed to assess the sealing ability of materials used for filling root canals [28][29][30] . An in vitro dye penetration test is usually used as an easy, quantitative method for assessing the leakage of materials used for endodontic filling [31][32] . An India ink solution is a potentially suitable tracer because some carbon particles have relatively similar sizes to bacteria, and thus would show similar degrees of penetration 29,33) .…”
Section: Discussionmentioning
confidence: 99%